New insight into the neuropsychiatric side effects of protease inhibitors. Issue 5 (September 2014) - Phipps, Emily; Miller, Alastair
<x xml:space="preserve">Abstract</x> The adverse effects of anti‐retroviral drugs should be considered by both medical and psychiatric clinicians for mental health problems in HIV positive patients. This case report describes the development of psychiatric complications in a patient recently commenced on protease inhibitors which then seemingly improved with a switch to an HIV integrase inhibitor.